Catalytic Prins Reaction Effected by Molecular Iodine in the Presence of Bis(trifluoromethanesulfonyl)imide Salts - Harnying, Wacharee; Neudörfl, Jörg-M.; Berkessel, Albrecht (Synthesis, 2017)
The Prins reaction is an efficient method for the direct generation of 1,3-dioxanes from alkenes and aldehydes. As first published in 2008, this process can be effected by stoichiometric amounts of molecular iodine. We herein report a catalytic protocol allowing the use of iodine at low loading (0.5–5 mol%), smoothly effecting the condensation of styrenes with aliphatic aldehydes to rac-1,3-dioxanes. Moreover, this mild catalytic system effects the isomerization of the 1,3-dioxane products to the thermodynamically favored one. As a result, substituted rac-1,3-dioxanes were prepared in high yields (up to 92%), and with high diastereoselectivities (d.r. up to 82:18). For the application of iodine in catalytic amounts, the addition of pyridinium bis(trifluoromethanesulfonyl)imide (TFSI) salts in a 1:1 ratio to iodine is the key to success.
Keywords: Prins reaction; catalysis; 1,3-dioxanes; molecular iodine; bis(trifluoromethanesulfonyl)imide salts